Fractal morphology of cement foams - Karam, G.N. (1993)
The fractal morphology of the microstructure of cement foams is studied. The pore sizes are shown to follow a fractal distribution. The solid skeleton is also found to be fractal and its fractal dimension is calculated for different densities. Deterministic and random models are proposed to model this microstructure.